Using wireless inter-PANs to enable seamless ongoing interaction across mobile meetings and dispersed settings. - Wiberg, M. (IEEE Network : the magazine of global information exchange)
This article presents results of a research project aimed at developing novel meeting support for mobile work domains. The system developed, called RoamWare, supports seamless ongoing interaction across collocated mobile face-to-face meetings and dispersed work settings by use of wireless inter-PANs. An inter-PAN is an ad hoc setup of several mobile devices belonging to different users. This article describes the design requirements for RoamWare, and how these have been realized in a working prototype system. RoamWare contributes to the fields of human-computer interaction and computer-supported cooperative work by illustrating how session management models can be modified to incorporate spontaneous mobile meetings into one ongoing session of interaction